2020
DOI: 10.28991/cej-2020-03091586
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage Behavior of Conventional and Nonconventional Concrete: A Review

Abstract: Concrete is indeed one of the most consumed construction materials all over the world. In spite of that, its behavior towards absolute volume change is still faced with uncertainties in terms of chemical and physical reactions at different stages of its life span, starting from the early time of hydration process, which depends on various factors including water/cement ratio, concrete proportioning and surrounding environmental conditions. This interest in understanding and defining the different types of shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Recycled aggregate has different properties than natural aggregates, therefore they behave differently in concrete mixtures [30]. Compressive strength, tensile strength and modulus of elasticity are the most effective properties of concrete affecting its performance properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recycled aggregate has different properties than natural aggregates, therefore they behave differently in concrete mixtures [30]. Compressive strength, tensile strength and modulus of elasticity are the most effective properties of concrete affecting its performance properties.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinkage behavior of rubberized concrete was investigated before as mentioned by Elzokra et al (2020). Yung et al (Yung et al, 2013) concluded in their study on the durability properties of self-compacted concrete including rubber powder that the shrinkage in RBC is small but larger than the control one, furthermore, the increase in shrinkage is directly proportional to the amount of rubber.…”
Section: Shrinkagementioning
confidence: 99%
“…Water absorption and water permeability is such a parameter which shows the transport way of water but also provide water resistance capacity of alkali activated binders and concretes. Researchers studied the influence of liquid alkali activator and use of silica fume (SF) on durability and microstructural properties of AASC pastes [49,[71][72][73][74][75]. The linear regression of porosity versus compressive is shown in Fig.…”
Section: Water Absorption and Water Permeabilitymentioning
confidence: 99%